Diode lasers with asymmetric barriers for 850 nm spectral range: experimental studies of power characteristics. (October 2015) - Zubov, F I; Zhukov, A E; Shernyakov, Yu M; Maximov, M V; Semenova, E S; Asryan, L V
Abstract: It is demonstrated that the use of asymmetric barrier layers in a waveguide of a diode laser suppress non-linearity of light-current characteristic and thus improve its power characteristics under high current injection. The results are presented for 850-nm AlGaAs/GaAs broad-area lasers with GaInP and AlInGaAs asymmetric barriers.